The Relationship between Teeth Brushing Behavior and Caries Incidence in Class 1 and 2 Students of Kampung Melayu 6 in 2022 - Cucuk Kunang Sari; Indah Yayu Qoriasih; Zahrah Maulidia Septimar (Journal of Smart Nursing and Health Science, 2023)
Background: Tooth brushing behavior is the act of cleaning the oral cavity and teeth from food residue using a toothbrush. The World Health Organization (WHO) in 2017 explained that the largest incidence of dental and oral problems was dental caries in children 60% to 90%. Caries is a disease of hard tissue (email, dentin) caused by the activity of microorganisms in carbohydrates that cannot be broken down. The main factors causing tooth decay are the host (teeth and saliva), substrate (food), caries caries-causing microorganisms, and time. The habit of brushing your teeth properly is the most effective way to tooth decay. Purpose: The purpose of this study was to determine the relationship between tooth-brushing behavior and the incidence of caries. Methode: This research method uses quantitative research with a cross-sectional research design and Data analysis using a total sampling method of 70 respondents at SDN Kampung Melayu 06 Tangerang in August and used Spearman rank correlation test analysis. Result: The results of this study indicate that there is a relationship between dental behavior and the incidence of caries with a P-value of 0.000 r = 0.477.